Antifungal activity in vitro and in vivo of extracts and lignans isolated from Larrea divaricata Cav. against phytopathogenic fungus - Vogt, Maria Veronica (2013)
The aim of this study was to evaluate the effectiveness of organic extracts and isolated compounds of the medicinal plant Larrea divaricata Cav. against phytopathogenic fungi. Chloroformic extract showed the highest antifungal activity and three compounds were identified in this extract: Apigenine-7-methylether (1), nordihydroguaiaretic acid (2) and 3,4′-dihydroxy-3′,4-dimethoxy-6,7′-cyclolignan (3). Compound 3 is described for the first time in the species and exhibited strong antifungal activity in vitro (Fusarium graminearum MIC = 15.6 μg/mL) and in vivo producing decreasing disease on glasshouse-grown wheat plants reducing damping-off (14% in pre emergency) and Severity Index from 2.6 upto 1.1. In this study it is clear that the application of botanical products from L. divaricata can be effective in the management of seedling blight and crown rot of wheat.